Ultrasound-detected connective tissue involvement in acute muscle injuries in elite athletes and return to play: The French National Institute of Sports (INSEP) study - Renoux, J.; Brasseur, J. L.; Wagner, M.; Frey, A.; Folinais, D.; Dibie, C.; Maiza, D.; Crema, M. D. (Journal of Science and Medicine in Sport, 2019)
Objectives: Previous MRI studies showed that involvement of connective tissue in muscle injuries may prolong recovery times. The relevance of ultrasound assessment of connective tissue involvement as a prognostic factor is unknown. The aim was to test the hypothesis that ultrasound-detected connective tissue involvement in acute muscle injuries are related to longer recovery times. Design: Cohort study. Methods: Seventy consecutive elite athletes from the French National Institute of Sports (INSEP) sustaining an acute muscle injury showing positive findings on ultrasound at baseline were included. Ultrasound was systematically performed within 7 days after the injury for the assessment of severity (grades 1-4) and type of injury in regard to the absence (M injuries) or presence (C injuries) of connective tissue involvement. The differences in the mean time needed to return to play (RTP) between the different grades and types of injury were assessed using multiple non-parametric tests. Results: When considering the overall grades independently of the type of injury (M or C), an increase in the mean time needed to RTP was observed with the increase of grades (p < 0.0001). The same relationship was found when considering grades from M and C injuries separately, with higher grades of injuries exhibiting longer times needed to RTP (p < 0.0001). Longer times needed to RTP were observed in athletes demonstrating C injuries in comparison to the ones exhibiting M injuries overall (p = 0.002). Conclusions: Ultrasound-detected connective tissue involvement in acute muscle injuries are related to longer times needed to RTP, especially when disruption is detected.